2018
DOI: 10.1371/journal.pntd.0006902
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis is associated with incident HIV transmission and death in Zambia

Abstract: BackgroundWe examined relationships between schistosome infection, HIV transmission or acquisition, and all-cause death.MethodsWe retrospectively tested baseline sera from a heterosexual HIV-discordant couple cohort in Lusaka, Zambia with follow-up from 1994–2012 in a nested case-control design. Schistosome-specific antibody levels were measured by ELISA. Associations between baseline antibody response to schistosome antigens and incident HIV transmission, acquisition, and all-cause death stratified by gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 50 publications
2
69
1
Order By: Relevance
“…Of the eight included observational studies, seven were cross-sectional studies [18][19][20]22,[29][30][31] and one was a nested case-control study [25]. All the studies were conducted in Africa-three from Zimbabwe, two from Tanzania, one each from Ghana, South Africa and Zambia.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the eight included observational studies, seven were cross-sectional studies [18][19][20]22,[29][30][31] and one was a nested case-control study [25]. All the studies were conducted in Africa-three from Zimbabwe, two from Tanzania, one each from Ghana, South Africa and Zambia.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…When a potentially relevant publication did not present needed information for meta-analysis, the authors were contacted to request additional data. If the dataset was publicly available, we obtained needed values directly [25].…”
Section: Study Selection and Data Extractionmentioning
confidence: 99%
“…FGS has been associated with infertility, a condition associated with negative social and psychological impacts in many low-income countries 6 . In addition, observational studies have suggested an association between FGS and prevalent HIV infection 7 , 8 , and HIV transmission and acquisition 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Egg deposition in the liver is associated with the formation of granulomas and subsequent serious complications (1). In addition, both adult schistosomes and deposited eggs induce immunomodulatory effects that impair the host immune defenses against other pathogens, such as human immunodeficiency and hepatitis B/hepatitis C viruses (3,4).…”
Section: [Le1] [Le1]mentioning
confidence: 99%